Understanding Virtual Team Interaction In Large, Complex Resource Projects - Norman, Francis; Pick, David (Engineers Australia, 2014)
The rapid growth in the use of distributed or virtual teams to execute engineering projects, ranging from relatively modest buildings and infrastructure through to multi-billion dollar resources mega-projects, has introduced entirely new layers and areas of complexity to the control and execution of the projects. These new challenges are generally poorly understood by the organizations undertaking the work and consequently tend to be managed on the run rather than designed out in the planning phases of their projects. Unanticipated problems during the execution of the projects often result in lost productivity and distraction of the project management team. This often occurs at critical phases, along with lost opportunities for the organizations to be able to take on additional projects as they deal with problems and delays. Many project delivery organizations, labouring under the procedures and processes developed over many decades to control and manage co-located projects, struggle to adapt to the requirements of the new organizational structures they have to have in place for the distributed teams of modern projects. They often find that traditional approaches leave them exposed to previously unforeseen execution risks. Additionally, new boundaries and battery limits introduced by the adoption of distributed execution methodologies has brought with them interpersonal interfaces that are completely new to many engineers, and which are rarely considered in the training of staff. These interfaces, both technical and human, if not properly considered and controlled can lead to communication breakdowns with resulting loss of productivity, errors and rework, putting the projects at greater risk. This paper draws on PhD research being conducted into interpersonal communications between virtual teams delivering engineering projects into the WA resources sector. This research is identifying a number of problems associated with the use of virtual teams and some solutions that are being adapted and developed. The paper outlines current problems being faced within resource projects and attempts to offer solutions which can provide ways to mitigate the risks and turn newly formed and existing virtual teams into high performing, stable and productive units.